Application of Team Game Tournament Cooperative Learning Type learning model (TGT) to improve the results of learning based basic techniques in students in the XII class of Sos 4 SMAN 6 Surakarta student year 2018/2019 - Muhammad Ishaq Saputro; Agus Kristyanto; Sunardi Sunardi (PJKR FKOR UNS, 2020)
This study aims to improve the learning outcomes of playing football in class XII Social Sciences 4 Surakarta Senior High School 6 of 2017/2018 Academic Year. This study uses the Classroom Action Research (CAR) method. This research was conducted in two cycles, with each cycle consisting of planning, action, observation, and reflection. The research subjects were students of class XII Social Sciences 4 of SMA N 6 Surakarta in the 2017/2018 Academic Year, which numbered 25 students with details of 10 male students 15 female students. Sources of data in this study come from teachers and students. The technique of collecting data is by testing and observing during the learning activities. The data analysis technique used in this study was descriptive based on qualitative analysis with percentages. From the analysis of the data obtained the following results: In the pre-cycle, the results of learning to play football students who completed reached 44% or as many as 11 students and students who have not completed 56% or as many as 14 students. In the first cycle, the results of learning to play football students who completed reached 68% or as many as 17 students and students who have not finished 22% or as many as 8 students. In the second cycle the learning outcomes of playing football students were completed 88% or 22 students and students who had not finished 12% or as many as 3 students. The implementation of actions in cycle I and cycle II lead to an active, effective, efficient and enjoyable learning process so that it can support the occurrence of quality learning. Based on the results of the study obtained conclusions that: learning through a tactical approach, can improve learning outcomes of playing football in class XIISos 4 Surakarta N SMA 6 2018/2019 Academic Year.